GE_GERICHTE P/3539/2009 vom 8. Juli 2009 - GE Cour de justice (2009)
; CONDITION DE RECEVABILITÉ ; OBJET DU RECOURS ; INTERPRÉTATION(PROCÉDURE) ; VISITE ; RISQUE DE COLLUSION ; PROPORTIONNALITÉ | CPP.190; CPP.34b